Enhancing Islamic Religious Learning and Quranic Reading Through KKN-Thematic Program: A Case Study in Ridan Permai Village - Pardosi, Fakhrurrozi; Sinaga, Sopian; Dasa Syawal Syahputra; Dori Chandra; Candra Gunawan; Zulham Effendi (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
This study evaluates the contribution of Thematic Community Service Program (KKN-T) students from the Islamic College (STAI) As-Sunnah in enhancing children's enthusiasm for Islamic religious learning and Quranic reading in Ridan Permai Village. Using a qualitative descriptive method with an Asset Based Community Development (ABCD) approach, data were collected before and after intervention through observation, interviews, and activity documentation. Results show significant improvements in children's enthusiasm for Islamic studies and Quranic reading abilities following KKN-T student interventions through various learning activities such as Quran memorization and tahsin circles, Arabic language learning, prophetic biography studies, ablution and adhan practice training, and Islamic competitions. Community participation in village religious activities also increased. These findings demonstrate that the KKN-T program can serve as an effective model for enhancing learning enthusiasm and community engagement in religious education at the local level.